A new species of the ant genus Forelius (Formicidae: Dolichoderinae) from the dry forest of Colombia - Guerrero, Roberto J.; Fernández, Fernando (Zootaxa, 2008)
Forelius damiani sp. nov. is described from the dry forest of the Sierra Nevada de Santa Marta, Colombia, and additional collections from Costa Rica and Texas (USA). This new species is separated from the other rounded spiracles Forelius by the number of erect pronotal hairs, size and coloration. Comments and hypotheses about the biogeography of the genus are provided. Forelius pruinosus is recorded for the first time for Colombia.